Identification of the Type of Feed for the Sumatran Elephant (Elephas maximus sumatranus) at the Elephant Response Unit (ERU) Camp Bukit Barisan Selatan National Park - Marhaeni, Agustina; Darmawan, Andy; Maretta, Gres; Subki (Indonesian Journal of Environment and Sustainability Issues, 2025)
This study aims to identify the types of plants consumed by Sumatran elephants, the parts they eat, and the most frequently consumed plant species as a basis for managing Sumatran elephant feed in the Camp Elephant Response Unit (ERU) area of Bukit Barisan Selatan National Park. Data was collected through direct observation from 09:00 to 15:00 WIB, with observation locations determined using the purposive sampling method. The collected data included the types of food plants, the parts consumed, and the most frequently eaten plant species. Data analysis was conducted by calculating the Sorensen species similarity index and the foraging frequency. A total of 30 plant species were identified as elephant food, with 19 species found in open land habitats. The highest plant species similarity index based on habitat type was found on mixed habitats with swamp openings and cover, reaching 63.15%. The highest plant species similarity index based on individual elephants was recorded for Haryono and Renold at 80%. Eight plant species were identified as the most frequently consumed, including Brachiaria mutica, Cyperus kyllingia, Fimbristylis sp., Imperata cylindrica, Paspalum conjugatum, Panicum repens, Rynchospora corymbosa, and Scleria sp. Additionally, elephants only foraged eight plant species for other functions. Based on this study, Sumatran elephant only consume plant species that are abundant within their grazing habitat. The findings of this study can support the ex-situ conservation of Sumatran elephant by ensuring the continued availability of their food plants in the Camp ERU area of Bukit Barisan Selatan National Park. Keywoards: Sumatran elephant; habitat; identification; foraging frequency; food plants